Local Accumulation of Axonal Mitochondria in the Optic Nerve Glial Lamina Precedes Myelination - Wilkison, Samantha J.; Bright, Cora L.; Vancini, Ricardo; Song, Daniel J.; Bomze, Howard M.; Cartoni, Romain (Frontiers in Neuroanatomy, 2021)
Mitochondria are essential for neurons and must be optimally distributed along their axon to fulfil local functions. A high density of mitochondria has been observed in retinal ganglion cell (RGC) axons of an unmyelinated region of the optic nerve, called the glial lamina (GL) in mouse (lamina cribrosa in human). In glaucoma, the world’s leading cause of irreversible blindness, the GL is the epicenter of RGC degeneration and is connected to mitochondrial dysfunction. It is generally accepted that the local accumulation of mitochondria in the GL is established due to the higher energy requirement of unmyelinated axons. Here we revisit the connection between mitochondrial positioning and myelin in RGC axons. We show that the high density of mitochondria in the GL is restricted to larger axons and is established before myelination. Thus, contrary to a longstanding belief in the field, the myelination pattern is not responsible for the establishment of the local accumulation of mitochondria in GL axons. Our findings open new research avenues likely critical to understanding the pathophysiology of glaucoma.